Occurrence and identification of Basidiomycetous Fomitopsis species the causal agent of Brown-rot in oil palm Elaeis guineensis in Johor, Malaysia - Muhammad Muhammad; Roswanira Abdul Wahab; Mohd Hefni Rusli; Fahrul Huyop (Journal of Tropical Life Science, 2022)
Macro fungi belonging to the family Ã¢â‚¬Å“PolyporaceaeÃ¢â‚¬Â in the phylum Basidiomycota are among the commonplace causal agents of plant diseases. In the present study, we reported the molecular characterization of a macro fungi basidiomycetous brown-rot fungal phytopathogen Fomitopsis strain MM4. The fungal phytopathogen was identified and molecular characterized from the infected stem and tissue of oil palm (Elaeis guineensis) in Kulai, Johor. The 18SrRNA nucleotide sequence of the fungal pathogen strain MM4 showed 99% similarity with partial sequences of Antrodia serialis maintained in the genebank database. The pairwise multiple sequence alignment and phylogenetic analysis revealed that the fungus clustered into a single branch of a phylogenetic tree; hence the fungus was designated as Fomitopsis meliae (MM4). The pathogenicity test revealed significant differences (p Ã¢â€°Â¤ 0.05) in disease severity caused by the characterized basidiomycetous brown-rot F. meliae fungal pathogen on oil palm seedlings and the pathogen was successfully re-isolated from infected samples. To the best of our knowledge, this is the first report of 18S rRNA F. meliae Basidiomycota brown-rot fungi infecting oil palm (Elaeis guineensis). The findings of this study thus support the diversity of pathogenic macro fungi affecting oil palm trees in Malaysia.